2017
DOI: 10.5424/sjar/2017151-9950
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plum rootstocks on agronomic performance, leaf mineral nutrition and fruit quality of ‘Catherina’ peach cultivar in heavy-calcareous soil conditions

Abstract: The agronomic performance and leaf mineral nutrition of the non-melting clingstone peach cv. 'Catherina' was evaluated on seven hexaploid plum rootstocks, as well as one Prunus persica seedling. They were assessed over a period of 15 years in a field trial at the Experimental Station of Aula Dei-CSIC (Zaragoza, Spain), located in the Ebro Valley (NE Spain). Growing conditions generated varying levels of tree mortality, the highest with Constantí 1, Monpol and Montizo, whereas all Adesoto, GF 655/2 and PM 105 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
39
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 41 publications
12
39
1
1
Order By: Relevance
“…A moderate to low negative significantly correlation was found between SPAD and Fe in this study. Nevertheless, our results were within the range as previously reported in other Prunus studies (Jiménez et al, 2008;Mestre et al, 2015Mestre et al, , 2017.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A moderate to low negative significantly correlation was found between SPAD and Fe in this study. Nevertheless, our results were within the range as previously reported in other Prunus studies (Jiménez et al, 2008;Mestre et al, 2015Mestre et al, , 2017.…”
Section: Discussionsupporting
confidence: 92%
“…In general, the leaf mineral concentrations appeared to be within the optimum range according to reference values (Reuter et al, 1997), with the exceptions of N, P, Fe and Mn. Leaf N values were slightly lower than the optimum, explained mainly by the type of soil (calcareous with a high pH), in good agreement with other studies in similar soil conditions (El-Jendoubi et al, 2012;Mestre et al, 2015Mestre et al, , 2017. Guo-yi et al (2015) reported that N influenced fruit size and composition, and higher N levels could decrease the amount of soluble solids and increase the titratable acid level in apples, which agrees with the correlations found in the present study between leaf N concentration and SSC and TA.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations